Isoniazid Loaded PCL-PEG Copolymer Nanoparticles for Sustained Release Application - Kulkarni, Alpana; Betai, Priya (Recent Advances in Anti-Infective Drug Discovery, 2023)
Background: Tuberculosis (TB) is still a major cause of death worldwide, despite possibly curable therapies. Neurotoxicity, optic neuritis, and severe liver damage are side effects of isoniazid, a powerful first-line anti-TB drug. Objective: We investigated the use of PCL-PEG copolymer to sustain the release of isoniazid to reduce its adverse effects. Methods: In the present work, PCL-PEG copolymer was synthesized and characterized. Isoniazid-loaded nanoparticles (Inp) were prepared using a PCL-PEG copolymer. Furthermore, a 23 half factorial design was employed for the optimization of drug and emulsifier concentration in Inp. Full characterization of the nanoparticles was performed in terms of drug loading, entrapment efficiency, particle size, zeta potential, and in vitro drug release. The morphology, FTIR, DSC, and PXRD evaluation of the optimized Batch Inp F13 were studied. Stability was evaluated by storing the freeze-dried Inp F13 at various temperatures. Results: The entrapment efficiency and drug loading of nanoparticles prepared by double emulsion solvent evaporation were found to be the highest. The release study revealed that all batches of nanoparticles exhibited sustained drug release (60.26 - 88.59%) for 5 days. The cytotoxicity study conducted on Mycobacterium tuberculosis revealed a gradual release of isoniazid from Inp, reaching the maximum (on the 15th day) compared to plain isoniazid (on the 4th day). At 0.8 μg/mL concentration, the inhibitory activity of Inp F13 was maintained for 15 days, indicating sustained release of isoniazid. Conclusion: The nanoparticles having PCL:PEG in a 95:5 ratio, with 0.5% PVA and initial drug loading of 3 mg, produced the optimum batch. Isoniazid-loaded PCL-PEG nanoparticles allowed controlled (sustained) release of isoniazid.
Keywords: tuberculosis